Prevalence of Pediatric and Adolescent Balance Disorders: Analysis of a Mono-Institutional Series of 472 Patients - Cristiano Balzanelli; Daniele Spataro; Luca Oscar Redaelli de Zinis (Children, 2021)
(1) Background: To assess the prevalence and frequency distribution of balance disorders in children and adolescents to delineate the planning of a targeted clinical and instrumental diagnostic work-up; (2) Methods: Retrospective analysis of the clinical documentation of patients under 18 years suffering from balance disorders from 2010 to 2019. Detailed collection of clinical history, accurate clinical examination, including both nystagmus and vestibulospinal signs examinations, and specific instrumental testing were the basis of the diagnostic process. (3) Results: A total of 472 participants were included in the study. Vestibular loss (26.1%) was the most frequent cause of vertigo in children, followed by vestibular migraine (21.2%) and benign paroxysmal positional vertigo (10.2%). In 1.1% of patients, the cause of vertigo remained undefined; (4) Conclusions: The diagnostic process applied was effective in understanding the cause of balance disorders in most cases and prevents more complex and expensive investigations reserved for only a few selected cases.